Respiratory and gastrointestinal management of an infant with a birth weight of 258 grams - Itoshima Ryo; Oda Arata; Ogawa Ryo; Yanagisawa Toshimitsu; Hiroma Takehiko; Nakamura Tomohiko (United States, 2025)
Background: Nowadays, more infants weighing ≤ 300 g are born, and they survive because of the improvements in neonatal care and treatment. However, their detailed clinical course and neonatal intensive care unit management remain unknown due to their low survival rate and dearth of reports. Case Presentation: A male infant was born at 24 weeks and 5 days of gestation and weighed 258 g. The infant received 72 days of invasive and 92 days of noninvasive respiratory support, including high-frequency oscillatory ventilation with volume guarantee and noninvasive neurally adjusted ventilatory assist. Meconium-related ileus was safely treated using diatrizoate. Although he was diagnosed with severe bronchopulmonary dysplasia and retinopathy of prematurity requiring laser photocoagulation, he had no other severe complications. He was discharged 201 days post-delivery (3 months of corrected age) with a weight of 3396 g. Conclusions: Although managing infants weighing ≤ 300 g is difficult, our experience shows that it is possible by combining traditional and modern management methods. The management of such infants requires an understanding of the expected difficulties and adaptation of existing methods to their management. The management techniques described here should help improve their survival and long-term prognosis.